Women in Theological Education - Badilla, Flore; Ngale, Angélique; Ibanda, Agnes (2025)
Interview with three Francophone African women, all having achieved PHDs in theology and serving in their local universities and churches. Mesa Global is bringing people around the table and fostering leaders serving the church. Learn more about how Mesa Global is using education to reach the nations with the Gospel.
free